Use of endobronchial valves in persistent air leaks: a case report and review of the literature. (February 2013) - Ambrosino, Nicolino; Ribechini, Alessandro; Allidi, Francesca; Gabbrielli, Luciano
Air leaks are observed after lung surgery, but can also occur spontaneously even in a previously normal lung. There are several available methods of management including, among others, chest drainage, Heimlich valves, surgical repair or pleural decortication. However, in some of these patients, surgery may be contraindicated. In this article, the authors report the use of one-way endobronchial valves in the treatment of a compromised patient with bullous emphysema who had previously undergone bullectomy. This approach resulted in improvement of dyspnea and exercise capacity. Use of endobronchial valves is an effective, nonsurgical, minimally invasive intervention for patients with prolonged pulmonary air leaks not suitable for surgical procedures.